La estrategia de atención primaria en salud desde la experiencia de enfermería en el departamento de boyacá - Sierra Forero, Libia Esperanza (Universidad Pedagógica y Tecnológica de Colombia, 2019)
Through this article will release the experience of strategy Primary Health Care (PHC) in Boyacá from the nursing profession. Given that Colombia has been a country, where experiences of the founding elements of PHC have had social, political and economic repercussions for decades and that is why early sought to integrate this strategy into the health system in the country. The main objective of the research is to critically analyze the information collected in the development of the nursing profession, highlight the com- monalities, differences, constraints, achievements and lessons learned. It starts from the concept of APS understood as Essential Health Care acces- sible to all individuals and families in the community by means acceptable to them, with their full participation and at an affordable cost to the community and the country and get to the conclusion that primary health care is the most important public health strategy.